Quantitative analysis and spatial and temporal distribution of volatile organic compounds in atmospheric air by utilizing drone with miniaturized samplers. (November 2021) - Lan, Hangzhen; Ruiz-Jimenez, Jose; Leleev, Yevgeny; Demaria, Giorgia; Jussila, Matti; Hartonen, Kari; Riekkola, Marja-Liisa
Abstract: Our second generation air sampling drone system, allowing the simultaneous use of four solid phase microextraction (SPME) Arrow and four in-tube extraction (ITEX) units, was employed for collection of atmospheric air samples at different spatial and temporal dimensions. SPME Arrow coated with two types of materials and ITEX with 10% polyacrylonitrile as sorbent were used to give a more comprehensive chemical characterization of the collected air samples. Before field sampling, miniaturized samplers went through quality control and assurance in terms of reproducibility (RSD ≤14.1%, N = 4), equilibrium time (≥10 min), breakthrough volume (1.8 L) and storage time (up to 48 h). 128 air samples were collected under optimal sampling conditions from July to September 2019 at the SMEAR II station and Qvidja farm, Finland. 347 VOCs were identified in the air samples either on-site or in the laboratory by thermal desorption gas chromatography - mass spectrometry, and they were quantified/semiquantified using Partial Least Squares Regression models. Individual models were developed for the different coatings and packing materials using gas phase standards obtained by an automatic permeation system. Average gas phase VOC concentrations ranged from 0.1 (toluene, the SMEAR II station) to 680 ng L −1 (acetone, Qvidja farm). Average VOC concentrations in aerosols ranged from 0.1 (1, 4-cyclohexadiene, the SMEAR II station) to 2287 ng L −1 (megastigma-4, 6, 8-triene, Qvidja farm). Clear differences in results were seen for samples collected at the SMEAR II station and Qvidja farm, between VOC compositions in gas phase and aerosols, and between the sampling site and height. Highlights: Air sampling drone system with GC-MS let VOC quantitation in gas phase and aerosols. PLSR models were utilized for the quantitation/semiquantitation of VOCs. Reliability of results was confirmed by quality control and assurance procedure. Differences between VOC composition in gas phase and aerosols were clarified. Statistical significant differences in VOCs were between sampling heights and sites.